Synthesis, crystal structure and antioxidant evaluation of N-(4-formylpiperazine-1-carbonothioyl)benzamide - Abosadiya, Hamza Milad (European Journal of Chemistry, 2020)
New benzoylthiourea derivative, N-(4-formylpiperazine-1-carbonothioyl)benzamide was prepared by the reaction of benzoylisothiocyanate with 1-piperazinecarboxaldehyde in acetone as solvent. The compound was characterized by FT-IR and multinuclear 1H and 13C NMR spectroscopy techniques. The benzoylthiourea molecule was obtained in crystalline form by recrystallization in DMSO. Single crystal X-ray diffraction study indicates that compound crystallized in triclinic crystal system and crystal data for C13H15N3O2S, space group P-1 (no. 2), a = 7.3016(9) Å, b = 7.7380(9) Å, c = 12.9815(16) Å, α = 103.581(4)°, β = 102.153(4)°, γ = 102.409(4)°, V = 669.46(14) Å3, Z = 2, T = 296(2) K, μ(MoKα) = 0.243 mm-1, Dcalc = 1.376 g/cm3, 31184 reflections measured (6.72° ≤ 2Θ ≤ 53.46°), 2822 unique (Rint = 0.0582) which were used in all calculations. The final R1 was 0.0501 (>2σ(I)) and wR2 was 0.1493 (all data). Intramolecular N-H···O hydrogen bond is stabilized the trans geometry of the thiono and the carbonyl groups. The heterocyclic piperazine ring makes a dihedral angle of 48.50(15)° with the benzene ring. Antioxidant test by DPPH method showed that compound exhibits good antioxidant activity of about 75%.